2021
DOI: 10.3390/ijms22168547
|View full text |Cite
|
Sign up to set email alerts
|

Chitin-Derived AVR-48 Prevents Experimental Bronchopulmonary Dysplasia (BPD) and BPD-Associated Pulmonary Hypertension in Newborn Mice

Abstract: Bronchopulmonary dysplasia (BPD) is the most common complication of prematurity and a key contributor to the large health care burden associated with prematurity, longer hospital stays, higher hospital costs, and frequent re-hospitalizations of affected patients through the first year of life and increased resource utilization throughout childhood. This disease is associated with abnormal pulmonary function that may lead to BPD-associated pulmonary hypertension (PH), a major contributor to neonatal mortality a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…Lung morphometry, including mean linear intercept (MLI), radial alveolar count (RAC), and septal thickness were calculated as previously described. 21 , 22 MLI was calculated using Image J software by measuring the average distance between the intersects of alveolar septal tissue and a superimposed counting grid. RAC was calculated as the number of septa intersected by each line drawn from the center of the respiratory bronchiole to the distal acinus.…”
Section: Methodsmentioning
confidence: 99%
“…Lung morphometry, including mean linear intercept (MLI), radial alveolar count (RAC), and septal thickness were calculated as previously described. 21 , 22 MLI was calculated using Image J software by measuring the average distance between the intersects of alveolar septal tissue and a superimposed counting grid. RAC was calculated as the number of septa intersected by each line drawn from the center of the respiratory bronchiole to the distal acinus.…”
Section: Methodsmentioning
confidence: 99%
“…Chemotaxis involves many chemokines, some of which are species- or cell-specific, and is initiated when soluble chemokines bind to their cognate receptors on immune cells ( Rossi and Zlotnik, 2000 ; Hughes and Nibbs, 2018 ). A number of studies have shown that dopamine can impact the production of chemotactic factors, particularly CCL2, which is important in the pathogenesis of many chronic inflammatory conditions, as well as neurologic HIV (neuroHIV) ( Eugenin et al, 2006 ; Covino et al, 2016 ; Fantuzzi et al, 2019 ; Das et al, 2021 ). Dopamine increased the mRNA expression of CXCL8 and CCL2 in activated PBMCs ( Torres et al, 2005 ) and the injection of a D1-like agonist increased the mRNA expression levels of CCL2 and C-C motif chemokine ligand 7 in the rodent PFC ( Saika et al, 2018 ).…”
Section: Dopamine and Immune Cellsmentioning
confidence: 99%
“…Bandari et al investigated the effects of chitin derivative compounds in alleviating lung inflammatory diseases such as acute lung injury (ALI), acute respiratory distress syndrome (ARDS) [ 1 ], and bronchopulmonary dysplasia (BPD) [ 2 ]. Although many efforts have been made to develop drugs to prevent or counteract these lung diseases, to date there are no effective cures available.…”
mentioning
confidence: 99%
“…BPD is an inflammatory disease characterized by high levels of cytokines, chemokines, and inflammatory cells in the lungs and blood serum, and plasma. Das et al [ 2 ] evaluated the safety and efficacy of AVR-48 as prophylactic therapy for preventing experimental BPD in a hyperoxia-induced experimental neonatal mouse model, using different routes of administration. AVR-48 was administered 2 and 4 days after birth.…”
mentioning
confidence: 99%